The Issue of Safeguarding State Secrets During the Preliminary Investigation Phase (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the specifics of the issue of securing state secrets at the preliminary investigation stage. The secrecy of the preliminary investigation, on the one hand, protects the rights and freedoms of the individual in the criminal process, and on the other hand, issues of protecting the interests of the state have been analyzed. Most importantly, at the preliminary investigation and inquiry stage, the issue of taking measures to prevent the disclosure of materials related to state secrets by the investigator was emphasized. This article analyzes national and foreign legislation as well as the opinions of scientists.